ST2 DI INFARK MIOKARD AKUT - Hery Priyanto; Jusak Nugraha; SP Edijanto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Acute Myocardial Infarction (AMI) is a major problem threatening Indonesian inhabitants as well as in many countries. Each year AMI patients are increasing. ST2 is a novel cardiac marker for the diagnosis and prognosis of acute myocardial infarction. The purpose of this study was to know and find the diagnostic value of ST2 serum in patients with AMI. This cross sectional study was conducted on 46 patients who had chest pain as the main complaint in the Emergency Department, Dr. Soetomo Hospital, Surabaya between April 20 to July 20, 2013. The sera were examined for ST2, cTn-T, the diagnostic value was determined using the acute myocardial infarction clinical criteria according to the Universal Definition of Myocardial Infarction (2007) as the gold standard. The results of ST2 serum levels measurement showed a sensitivity of 83% and specificity of 70% at a cut-off value of ST2 16.64 ng/mL and AUC 0.878, p=0.000. The concordance examination between using cTn-T levels and ST2 was 48.1%. A significanct correlation was obtained with a correlation coefficient r=0.489, p=0.001 between the levels of cTn-T and ST2. Based on this study, the ST2 serum levels can be used for screeningto aid the diagnosis of acute myocardial infarction. However, there is a weak correlation and concordance between cTn-T with ST2. Thus, the researchers need a further study to determine the diagnostic value of ST2 for the detection of acute myocardial infarction.